Mediation analysis with categorical independent variables. (1st January 2012) - Kang, Hyoung-Kil; Lee, Eunsoon
The primary goal of mediation analysis is to explicate the mechanism that underlies an observed relationship between an independent variable and a dependent variable by including a third explanatory variable, known as a mediator variable. While the concept of mediation is theoretically appealing, our literature study indicates that there has not been a comprehensive research work on how a categorical variable is assessed in the statistical mediation analysis of time and perceived quality of life. The main objective of this paper is two-fold. First, this paper develops conceptual justifications of employing psychological variables to represent unique constructs with as little conceptual overlap as possible in the mediation analysis to prevent multicollinearity issues. Second, a modified approach is then proposed to estimate relative direct and indirect effects as well as relative total effects between a categorical independent variable and a dependent variable. A numerical example is provided to facilitate the proposed approach.